Evaluasi Evaluasi Kesesuaian Lahan Untuk Komoditas Tanaman Kakao (Theobroma Cacao L.) Di Kecamatan V Koto Kampung Dalam Kabupaten Padang Pariaman Provinsi Sumatera Barat - Muzella, Febi (JURNAL BUANA, 2026)
This study aims (1) to determine the characteristics of land for cocoa plants in V Koto Kampung Dalam District, Padang Pariaman Regency. (2) to determine the distribution of land suitability for cocoa plants in V Koto Kampung Dalam District, Padang Pariaman Regency. This type of research is quantitative and to evaluate land suitability using the matching method with land suitability parameters in the form of soil, topography and climate. Based on the results of the study, it was found that (1) Land characteristics in V Koto Kampung Dalam District have rainfall that is not suitable for cocoa plants which is dominated by >3000 mm per year, and dominant soil conditions are quite suitable for cocoa plant growth requirements but there are a few areas that have obstacles in inappropriate drainage and rough soil texture, and for slope conditions are predominantly in accordance with cocoa plant growth requirements. (2) The level of land suitability for cocoa plants in V Koto Kampung Dalam District has various suitability classes consisting of 3 classes, namely quite suitable (S2) with an area of ​​640.82 Ha or 89.2% consisting of Nagari West Sikucua, North Sikucua, Central Sikucua, East Sikucua, South Campago, West Campago, and Campago, marginal land suitability class (S3) with an area of ​​773.06 Ha or 0.76% consisting of Nagari West Sikucua, Central Sikucua, Sikucua, Campago, West Campago, and South Campago and not suitable (N) with an area of ​​2.2 Ha or 0.03% consisting of Nagari Sikucua, East Sikucua, and West Sikucua.